Unveiling iodine-based electrolytes chemistry in aqueous dye-sensitized solar cells. Issue 8 (27th April 2016) - Bella, F.; Galliano, S.; Falco, M.; Viscardi, G.; Barolo, C.; Grätzel, M.; Gerbaldi, C.
Abstract : The chemistry behind the I − /I3 − redox couple is thoroughly investigated in 100% aqueous dye-sensitized solar cells, paving the way to this emerging green PV technology. Abstract : Aqueous dye-sensitized solar cells (DSSCs) have recently emerged as promising systems, which can combine low cost and environmental compatibility with appreciable efficiency, long-term durability and enhanced safety. In the present study, we thoroughly investigate the chemistry behind the iodide/triiodide-based redox mediator, which presents – in a completely aqueous environment – several differences when compared to the behavior observed in the conventionally used organic solvents. The speciation of ions, the effect of the concentration of the redox mediator and the type of counter-ion are characterized from the electrochemical, spectroscopic, photovoltaic and analytical viewpoints. Furthermore, we demonstrate that aqueous DSSCs, often assumed as unstable, hold the potential to assure unparalleled stability after five months of aging without any addition of stabilizers or gelling agents, thus envisaging the construction of eco-friendly photovoltaic devices free of expensive, flammable and toxic solvents.